An interdisciplinary intervention program to prevent early childhood caries in the Dominican Republic - Abreu-Placeres, Ninoska; Ekstrand, Kim Rud; Garrido, Luis Eduardo; Bakhshandeh, Azam; Martignon, Stefania (Frontiers in Oral Health, 2023)
Objective The principal aim of this randomized clinical trial (RCT) was to test the effectiveness in the prevention of Early Childhood Caries (ECC) through an educational intervention program with the use of a printed guide for pediatricians and parents both designed by pediatric dentists. Materials and methods After ethical approval, the first step was to design the educational guides, which were based on the information obtained from a focus group with pediatricians (n = 3), phone interviews with mothers to toddlers' (n = 7), and the best evidence available about children's oral health. For the RCT, 309 parents with their 10–12 months old children were randomly allocated to either the intervention or the control group. Parents in the intervention group received oral health education from the pediatricians supported by the printed guides. Parents in both groups received an oral health kit with a toothbrush and toothpaste at the first visit as well as at each 6-month follow-up visit. After 18 months the children were evaluated using ICDAS criteria. Results At baseline, data were available from 309 children (49.8% girls). The mean age of the children was of 10.8 months (SD = 0.8) and 69.3% had not had their teeth brushed with toothpaste. After 18 months, a total of 28 (22%) children in the intervention group and 44 (24%) in the control group were clinically examined. Regarding the number of tooth surfaces with caries lesions, the children in the intervention group had a mean of 6.50 (SD = 6.58) surfaces, while the children in the control group had a mean of 5.43 (SD = 4.74) surfaces with caries lesions. This difference was not significant (p = 0.460). Conclusion The RCT showed no effectiveness in caries-progression control. Despite this result, this study managed to identify barriers that do not allow pediatricians from offering parents adequate oral health recommendations. With this learning, it is possible to work on collaborative programs with pediatricians that over time likely will increase dental health by controlling for ECC.